2019
DOI: 10.22328/2077-9828-2019-11-2-75-83
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Structure of Hiv-1 Drug Resistance Among Treatment Naïve Patients Since the Introduction of Antiretroviral Therapy in the Russian Federation

Abstract: Aim: to analyze the prevalence, structure of drug resistance and drug resistance mutations in the protease and reverse transcriptase genes of HIV-1 among treatment naïve patients.Materials and methods. We analyzed protease and reverse transcriptase sequences from 1560 treatment naïve HIV-infected patients from all Federal Districts of the Russian Federation with the first positive immune blot during 1998–2017. Sequences were analyzed for the presence of drug resistance mutations and predicted drug resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
2
12
2
1
Order By: Relevance
“…The highest prevalence of TDR was found in patients from the central district (10.3%), which is most likely explained by the longer and wider use of ART compared to other districts. Earlier studies revealed that the prevalence of TDR has significantly increased in past few years due to ART becoming more available and has already reached 6,1% in 2016 [30]. Comparatively, higher prevalence of TDR was found in Eastern European countries.…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence of TDR was found in patients from the central district (10.3%), which is most likely explained by the longer and wider use of ART compared to other districts. Earlier studies revealed that the prevalence of TDR has significantly increased in past few years due to ART becoming more available and has already reached 6,1% in 2016 [30]. Comparatively, higher prevalence of TDR was found in Eastern European countries.…”
Section: Discussionmentioning
confidence: 99%
“…In this region, nationwide estimates of DR are not available, and data about the prevalence, pattern, and trend of HIV DR are very sparse and scattered. A number of studies conducted in Russia showed an increase in the prevalence of HIV DR among naïve patients from 0-1.5% in 1998-2014 [18,19] to 5.3% in a recent study [20]. In other EECA countries, there were limited or nonexistent data.…”
Section: Introductionmentioning
confidence: 99%
“…We observed similar issue in Russia, where the frequency of the E138A polymorphic mutation in patients infected with the dominant HIV A6 virus ranges from 4 to 8%. This mutation is not associated with the transmission of resistant viruses, since the frequency of its occurrence before the use of RPV and ETR in Russia (until 2011) differed marginally from that in the subsequent time period [30].…”
Section: Discussionmentioning
confidence: 90%